Eclampsia in Australia and New Zealand: A prospective population‐based study. (16th December 2019) - Pollock, Wendy; Peek, Michael J.; Wang, Alex; Li, Zhuoyang; Ellwood, David; Homer, Caroline S.E.; Jackson Pulver, Lisa; McLintock, Claire; Vaughan, Geraldine; Knight, Marian; Sullivan, Elizabeth A.
Abstract : Background: Eclampsia is a serious consequence of pre‐eclampsia. There are limited data from Australia and New Zealand (ANZ) on eclampsia. Aim: To determine the incidence, management and perinatal outcomes of women with eclampsia in ANZ. Materials and Methods: A two‐year population‐based descriptive study, using the Australasian Maternity Outcomes Surveillance System (AMOSS), carried out in 263 sites in Australia, and all 24 New Zealand maternity units, during a staggered implementation over 2010–2011. Eclampsia was defined as one or more seizures during pregnancy or postpartum (up to 14 days) in any woman with clinical evidence of pre‐eclampsia. Results: Of 136 women with eclampsia, 111 (83%) were in Australia and 25 (17%) in New Zealand. The estimated incidence of eclampsia was 2.2 (95% confidence interval (CI) 1.9–2.7) per 10 000 women giving birth. Aboriginal and Torres Strait Islander women were over‐represented in Australia ( n = 9; 8.1%). Women with antepartum eclampsia ( n = 58, 42.6%) were more likely to have a preterm birth ( P = 0.04). Sixty‐three (47.4%) women had pre‐eclampsia diagnosed prior to their first eclamptic seizure of whom 19 (30.2%) received magnesium sulphate prior to the first seizure. Nearly all women ( n = 128; 95.5%) received magnesium sulphate post‐seizure. No woman received prophylactic aspirin during pregnancy. Five women had a cerebrovascular haemorrhage, and there were five known perinatal deaths. Conclusions: Eclampsia is an uncommon consequence of pre‐eclampsia in ANZ. There is scope to reduce the incidence of this condition, associated with often catastrophic morbidity, through the use of low‐dose aspirin and magnesium sulphate in women at higher risk.